2015
DOI: 10.5433/1679-0359.2015v36n4p2893
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility of diets and nutritional value of torula yeast (Candida utilis) for rabbits (Oryctolagus cuniculus) and agoutis (Dasyprocta spp.)

Abstract: The aim of this study was to assess the nutritional value of diets that contain torula yeast in rabbits and agoutis and the influence of torula yeast on the apparent digestibility of the nutrients. In the first experiment, 32 New Zealand White rabbits were fed diets with four different levels (0%, 5%, 10%, and 15%) of torula yeast that was substituted for soybean meal. The experimental design was completely randomized with four treatments and eight repetitions. The digestibility coefficients (DC) of dry matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…These behaviors served as a reference to assess the animals' adaptability to their environment and to ensure that no behavioral factor was interfering with their reproductive physiology; the lack of such interference was demonstrated by the results showing that the duration of the estrous cycle was similar to the mean duration for the genus [28]. Corroborating data obtained by other researchers [1011] has shown that estrous cycle duration is species-dependent but varies from one female to another within the same species. Although confined in the same environment, synchronization of the estrous cycles, due to a male effect among the females, was not observed in this study, although it has been reported in other studies on reproductive management in domestic animals [141619].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These behaviors served as a reference to assess the animals' adaptability to their environment and to ensure that no behavioral factor was interfering with their reproductive physiology; the lack of such interference was demonstrated by the results showing that the duration of the estrous cycle was similar to the mean duration for the genus [28]. Corroborating data obtained by other researchers [1011] has shown that estrous cycle duration is species-dependent but varies from one female to another within the same species. Although confined in the same environment, synchronization of the estrous cycles, due to a male effect among the females, was not observed in this study, although it has been reported in other studies on reproductive management in domestic animals [141619].…”
Section: Discussionmentioning
confidence: 89%
“…That alternative is already a reality [17], especially in countries such as Brazil where hunting is not allowed and access to wild animal meat is obtained clandestinely. Such wild animal rearing practices indirectly help the conservation of the species in nature, because they provide an established legal market for animals born in captivity and raised for a predetermined purpose, potentially ending the practice of illicit hunting in countries where hunting is not permitted [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, fat content of the TY used in the current work was higher than all other reports (0.9% to 3.37%; Ringrose, 1949 ; Olvera-Novoa et al, 2002 ; Øverland et al, 2013 ; Lagos and Stein, 2020 ), and almost double the next leading amount (3.37% DM basis; Lagos and Stein, 2020 ). Differences in the nutrient composition of TYs are not surprising, as they have been grown under a wide range of conditions ( Buerth et al, 2016 ) and cultivated on a variety of different substrates including beet pulp ( Athar et al, 2009 ), distillery waste ( García et al, 2014 ; Hosken et al, 2015 ), pineapple effluent ( Nigam, 1998 ), and wheat bran ( Yunus et al, 2015 ) among others; whereas, the particular yeast used in the present experiment was grown on forestry byproducts from the timber industry.…”
Section: Discussionmentioning
confidence: 99%